The extent of extracurricular activity engagement in Jordanian secondary schools: A teacher’s perspective - Mansour, Othman Naser; Hasouneh, Osama Adel; Ibrahim, Nahla Abbas Hilmi; Al-Saud, Khaled (Journal of Education and e-Learning Research, 2025)
Extracurricular activities play a critical role in the holistic development of students, fostering not only academic success but also their social and emotional well-being. Despite their well-documented benefits, the extent to which extracurricular activities are implemented in schools can vary significantly. This study aims to assess the degree of extracurricular activities practiced in Jordanian secondary schools from the perspective of teachers. A descriptive survey research method was employed. A sample of 252 teachers was selected through random convenience sampling. Data were collected using a 27-item questionnaire developed specifically for the study. The results indicate that the overall practice of extracurricular activities in secondary schools is at a low level, with an overall mean score of 1.63. Planning extracurricular activities ranked first, with a mean score of 1.71 (low level). Organizing extracurricular activities ranked second, with a mean score of 1.64 (low level). Follow-up and evaluation of extracurricular activities ranked last with a mean score of 1.53 (low level). The study reveals that extracurricular activities are practiced at a low level in secondary schools. To improve this, the study recommends that the Ministry of Education provide clear guidance to help schools better plan and organize these activities, thereby enhancing their role in student development.